1997
DOI: 10.1086/514065
|View full text |Cite
|
Sign up to set email alerts
|

Urovirulence Determinants inEscherichia coliStrains Causing Prostatitis

Abstract: To define the urovirulence properties of Escherichia coli strains producing prostatitis, E. coli strains isolated from men with acute (7 strains) or chronic (23) prostatitis were compared with E. coli isolates from women with pyelonephritis (30), acute cystitis (60), or complicated urinary tract infection (UTI; 30). Strains from prostatitis patients were significantly more likely to express hemolysin than were strains causing complicated UTI (73% vs. 43%; P = .02) and more often demonstrated hybridization with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(13 citation statements)
references
References 19 publications
1
10
1
1
Order By: Relevance
“…Finally, in the present study, the presence of toxins was significantly higher in isolates from men compared to women, and in isolates of ST73 compared to ST69. A high frequency of toxin producing in UTI isolates from men was also noticed by others (Andreu et al 1997). …”
Section: Discussionsupporting
confidence: 81%
“…Finally, in the present study, the presence of toxins was significantly higher in isolates from men compared to women, and in isolates of ST73 compared to ST69. A high frequency of toxin producing in UTI isolates from men was also noticed by others (Andreu et al 1997). …”
Section: Discussionsupporting
confidence: 81%
“…S3 in the supplemental material). We assayed four available, previously described strain collections, the ECOR (16), Andreu prostatitis (17), Johnson urosepsis (18), and Mand STEC (9) collections. On the basis of these analyses, we observed that some strains have iraL alone (like CFT073), some have iraM alone (like K-12), some have both iraL and iraM , and others have neither iraL nor iraM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, the hemolysin phenotype, cnf1 gene, and P fimbriae have been found to be associated with prostatitis. 1 …”
Section: Discussionmentioning
confidence: 99%